2017
DOI: 10.1007/s00394-017-1573-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus coryniformis K8 CECT5711 on the immune response to influenza vaccination and the assessment of common respiratory symptoms in elderly subjects: a randomized controlled trial

Abstract: The administration of L. coryniformis K8 CECT5711 to an elderly population increased the immune response against the influenza vaccine and decreased symptoms associated with respiratory infections. Probiotic administration may be a natural and safe strategy to improve the efficacy of vaccines and to protect against common respiratory infections in susceptible populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
5
34
0
Order By: Relevance
“… 2013 ; Fonollá et al. 2019 ). We also observed a shorter duration of medication, probably due to less severe URTI symptoms, though the duration of sick leave did not significantly change between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“… 2013 ; Fonollá et al. 2019 ). We also observed a shorter duration of medication, probably due to less severe URTI symptoms, though the duration of sick leave did not significantly change between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that probiotic with regulating the balance of intestinal microecology exerts prophylactic and alleviating effects on diseases, such as allergic asthma [ 20 , 21 ], atopic dermatitis [ 22 , 23 ], and influenza infection [ 24 , 25 ], but the correlation between clinical characters of influenza infection and gut microbial alteration needs to be explained. Based on the gut–lung axis theory, the bi-directional cross-talk between lung and gut intricately influences the homeostasis of both [ 26 ], and therefore, the deeper understanding of gut microbial alteration on alleviating respiratory disorders contributes to therapeutic applications using probiotic strains.…”
Section: Discussionmentioning
confidence: 99%
“…infantis 10 9 and 8 g Gluco-Oligosaccharide for 8 weeks. Vaccine challenge at week 4 In vitro flu-vaccine antigen recall challenge No significant result Fonolla et al [ 136 ] R DB PC n = 98 Nursing home residents 83 ± 6 3.10 9 Lactobacillus coryniformis K8 CECT5711 daily capsule for 2 weeks prior vaccination Trivalent influenza vaccine response and incidence or severity of influenza-like illness (ILI) Higher seroconversion rate and reduced medication intake and incidence of ILI over a follow-up of 5 months Fukushima et al [ 137 ] R DB PC n = 24 Hospitalized elderly patients 84 ± 6 Enteral supplement feeding with fermented milk (89 kcal/d) containing 10 9 probiotic Lactobacillus johnsonii La1 for 12 weeks Incidence of infection Reduction in the number of days with infection. Improvement in the nutritional status.…”
Section: General Hallmarks Of Immune Agingmentioning
confidence: 99%